2016
DOI: 10.3390/w8050207
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Origins and Circulation Patterns Based on Isotopes in Challapampa Aquifer, Bolivia

Abstract: Aridity and seasonality of precipitation are characteristics of the highland region in Bolivia. Groundwater becomes an important and safe source of water when surficial bodies are intermittent and affected by natural and anthropogenic contamination. Decades of exploitation of the Challapampa aquifer, combined with lack of information required to understand the groundwater circulation, represent a challenge for reservoir management. This study analyzes isotopic compositions of deuterium and oxygen-18 in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The shallow groundwater is the response of the rainfall and any change in the rainfall will affect the ground water level and the water quality [39]. Similarly, [40] found that increase in rainfall increased human exposures to agricultural contaminants like waterborne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The shallow groundwater is the response of the rainfall and any change in the rainfall will affect the ground water level and the water quality [39]. Similarly, [40] found that increase in rainfall increased human exposures to agricultural contaminants like waterborne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The electromagnetic surveys in the study area aim to acquire characteristics of the subsurface at different depths expressed as resistivity; this feature is strongly influenced by the salinity of water stored in the voids. The average EC in the porous aquifer is 1.0 mS/cm (Gómez et al 2016) and the resistivity of the unconsolidated and saturated sediments vary from 10 to 20 Ω-m, according to Fig. 7.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, hydrochemical and isotopic characteristics were used to propose four flow systems in the middle of the alluvial fan (Gómez et al 2016), which are summarized in Table 1.…”
Section: Hydrogeologymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to estimate hydraulic properties, pumping tests were performed at some boreholes and the reported K values are in the range of 5.5 Â 10 À5 to 2.9 Â 10 À4 m/s (SCIDE et al 1996;Canaviri 2011). The hydrochemical analyses encompass major ion concentrations and in situ measurements, like pH and electrical conductivity (EC) (Lizarazu et al 1987;Swedish Geological AB 1996;Gómez et al 2016). The groundwater salinity in the study area, expressed as EC, is in the range of 0.8 to 3.5 mS/cm; however, only a few sites close to a fault reported the highest values, with the rest of the boreholes reporting values of 1.0 mS/cm.…”
Section: Theory Methods and Materialsmentioning
confidence: 99%